Nurses' knowledge of Diagnostic-Therapeutic Care Pathways (DTCP): A cross-sectional study - Ubaldino Ubaldi; Valentina Accinno; Margherita Ascione; Concetta Pane (OPI Napoli, 2022)
Introduction: Management by processes and clinical care pathways are now fundamental and indispensable requirements for quality improvement in healthcare organisations. The basic idea is to design a system that allows for continuous improvement in the way in which the key player in healthcare, i.e. the patient, is managed. If this were to happen, the best experiences to date tell us, it would definitively improve outcomes, efficiency and appropriateness. Moreover, patients perceive and appreciate this difference, allowing health professionals to operate at their best. Objective: To assess the knowledge and application of the DTCPs by the nursing staff. Materials and methods: The cross-sectional study took place in the period between June and September 2019 at the Operative Units of digestive surgery, hepatobiliary surgery, breast surgery and gynaecological surgery of the "Fondazione Policlinico Gemelli IRCCS in Rome". A questionnaire was administered only to permanent nurses. Results: A total of 64 questionnaires were administered of which 27 were correctly completed (response rate 42.1%) and considered valid for analysis. The sample of respondents was predominantly female (74.07%), 81.48% held a Bachelor's degree and 40.74% held a Master's degree. 55.56% knew what DTCPs were, but there was no in-depth knowledge of them in the sample. In fact, 55.56% knew whether there were active DTCPs in their region; 7.41% that nurses cannot participate in DTCPs and only 11.11% that nurses cannot participate in the review of individual DTCPs, while 59.26% were aware of the professional figures involved in the drafting and review of DTCPs. 25.93% knew what the diagnostic phase was based on and 14.81% that there were no active memoranda of understanding with public or private facilities in the diagnostic phase. Finally, only 25.93% were aware that the user could not be used in the evaluation of the outcome. Conclusions: Although the interviewees were familiar with clinical care pathways, for most of them there had never been active involvement, they agreed on user involvement instead.